A theorem on the removal of boundary singularities of pseudo-holomorphic curves - Fuchs, Urs; Qin, Lizhen (The journal of symplectic geometry, 2015)
We prove a theorem on the removal of singularities on the boundary of a pseudo-holomorphic curve. This theorem needs no assumption on the area of the curve.